Video Tracking Using Dual-Tree Wavelet Polar Matching and Rao-Blackwellised Particle Filter. (22nd February 2010) - Pang Pang, Sze Kim Sze Kim; Nelson Nelson, James D. B. James D. B.; Godsill Godsill, Simon J. Simon J.; Kingsbury Kingsbury, Nick Nick
Abstract : We describe a video tracking application using the dual-tree Polar Matching Algorithm. We develop the dynamical and observation models in a probabilistic setting and study the empirical probability distribution of the Polar Matching output. We model the visible and occluded target statistics using Beta distributions. This is incorporated into a Track-Before-Detect (TBD) solution for the overall observation likelihood of each video frame and provides a principled derivation of the observation likelihood. Due to the nonlinear nature of the problem, we design a Rao-Blackwellised Particle Filter (RBPF) for the sequential inference. Computer simulations demonstrate the ability of the algorithm to track a simulated video moving target in an urban environment with complete and partial occlusions.